URBAN FARMING DAN KETAHANAN PANGAN DI MASA PANDEMI: PENGENALAN TEKNIK BUDIDAYA HIDROPONIK DI KELURAHAN KERTAJAYA SURABAYA - Syifa Syarifah Alamiyah; Sandra Berliana Dewi; Achmad Habib Dwi Prakoso; Mahmudalia Rosa Yulaicho (Journal Publicuho, 2021)
PPKM (Enforcement of Restrictions on Community Activities) and the Kampung Tangguh Program are one of its policies. With the formation of this policy, the community is also encouraged to carry out productive activities even from home. Some of the growing trends are the existence of urban farming which is often used in urban areas that are quite densely populated. Besides being useful in food security, urban farming also helps the productivity of the community. Kuliah Kerja Nyata is an activity from the Universitas Pembangunan Nasional “Veteran” Jawa Timur in an effort to serve the community in the midst of the COVID-19 pandemic. Students do community service in RT I RW XI Kelurahan Kertajaya, Kecamatan Gubeng, Surabaya City by implementing an introduction to hydroponic cultivation techniques and education that are easy and can be done by the community. The purpose of doing community service by KKN students themselves is so that the community can be helped by the community service carried out by students and can create resilience in the food sector. The method used in this paper uses the results of observations and direct interviews with local residents. And the results of hydroponics are expected to inspire the community in developing hydroponics independently.